2003
DOI: 10.1046/j.1365-2222.2003.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

Intake of unsaturated fatty acids and HDL cholesterol levels are associated with manifestations of atopy in adults

Abstract: There is indication that HDL cholesterol also plays a role in the complex interaction of fat intake, metabolism and the manifestation of atopy in adults. These findings may contribute to the understanding of time trends and regional differences of allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
67
4
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 23 publications
13
67
4
1
Order By: Relevance
“…Although prior studies have also assessed the relationship between serum HDL-C and asthma, the results have been heterogeneous with serum HDL-C levels either being increased, decreased, or unchanged in subjects with asthma (20,(43)(44)(45)(46)(47)(48)(49)(50). Similar to our findings, prior studies have also not found a change in serum LDL-C in subjects with asthma, whereas TC was either decreased or unchanged and TG levels were either increased or unchanged.…”
Section: Discussionsupporting
confidence: 80%
“…Although prior studies have also assessed the relationship between serum HDL-C and asthma, the results have been heterogeneous with serum HDL-C levels either being increased, decreased, or unchanged in subjects with asthma (20,(43)(44)(45)(46)(47)(48)(49)(50). Similar to our findings, prior studies have also not found a change in serum LDL-C in subjects with asthma, whereas TC was either decreased or unchanged and TG levels were either increased or unchanged.…”
Section: Discussionsupporting
confidence: 80%
“…Contradictory effects of single fatty acids may have annihilated the effects of the fatty acid families. Furthermore, the allergic component in the present asthma cases might have been secondary (Schafer et al, 2003). Heinrich et al (2001) observed an inverse association between fruit intake and allergic sensitization while no association with vegetable consumption was found.…”
Section: Discussionmentioning
confidence: 60%
“…According to some reports cholesterol has no association with the pathogenesis of asthma [50,51]. However, few workers have shown that cholesterol level is elevated in asthmatic patients and can help to evaluate the effect of treatment [52,53].…”
Section: Insights In Chest Diseasesmentioning
confidence: 99%